VD_FINDINFO Décision / 2015 / 486 vom 19. Juni 2015 - VD Tribunal cantonal (2015)
NON-LIEU, VOIES DE FAIT, LÉGITIME DÉFENSE, EXCÈS, VIOLATION DE DOMICILE | 15 CP, 16 al. 1 CP, 52 CP, 310 CPP (CH), 8 CPP (CH)